Effect of training on morphological, physiological and biochemical variables of under 23 years soccer players - Manna, I.; Khanna, G. L.; Dhara, P. C. (International Journal of Sports Science and Engineering, 2013)
Purpose of the study was to find out the effect of training on selected morphological, physiological and biochemical variables of under 23 years soccer players. A total of 30 Indian male under 23 years soccer players (U23, age: 19.00-22.99 yr, mean age: 20.9 ± 1.0 yr playing for last 8-11 years) volunteered for this study. The training sessions were divided into 2 phases (i) Preparatory Phase (PP, 8 weeks) and (ii) Competitive Phase (CP, 4 weeks). The training programme consist of aerobic, anaerobic and skill development, and were completed 4 hrs/day; 5 days/week. Selected morphological, physiological and biochemical variables were measured at zero level (baseline data, BD) and at the end of PP and CP. A significant increase (P<0.05) in VO2max, anaerobic power, grip and back strength, urea and uric acid levels; and a decrease (P<0.05) in percent body fat, hemoglobin, total cholesterol, and triglyceride levels have been noted in PP and CP when compare to BD. However, no significant change was noted in stature, body mass, lean body mass, maximal heart rate, HDL-C and LDL-C levels of the players after the training. This study would provide useful information for training and selection of soccer players of under 23 age groups.